2016
DOI: 10.1002/2016gl069740
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous storm time equatorward and poleward large‐scale TIDs on a global scale

Abstract: We report on the first simultaneous observations of poleward and equatorward traveling ionospheric disturbances (TIDs) during the same geomagnetic storm period on a global scale. While poleward propagating TIDs originate from the geomagnetic equator region, equatorward propagating TIDs are launched from the auroral regions. On a global scale, we use total electron content observations from the Global Navigation Satellite Systems to show that these TIDs existed over South American, African, and Asian sectors. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 41 publications
3
43
1
Order By: Relevance
“…They are induced by low-frequency fast moving traveling atmospheric disturbances with wavelengths of several thousand kilometers that can propagate over large distances. Such high velocities are typical of LSTIDs (Dashora et al, 2009;Habarulema et al, 2016;Ngwira, McKinnell, Cilliers, & Coster, 2012). Our claim on the excitation of these LSTIDs is supported by observations and derived quantities in Figure 1.…”
Section: 1029/2018ja026172supporting
confidence: 85%
See 2 more Smart Citations
“…They are induced by low-frequency fast moving traveling atmospheric disturbances with wavelengths of several thousand kilometers that can propagate over large distances. Such high velocities are typical of LSTIDs (Dashora et al, 2009;Habarulema et al, 2016;Ngwira, McKinnell, Cilliers, & Coster, 2012). Our claim on the excitation of these LSTIDs is supported by observations and derived quantities in Figure 1.…”
Section: 1029/2018ja026172supporting
confidence: 85%
“…For instance, Habarulema et al (2016) suggest that changes in E×B vertical drift after the storm onset could be the source of poleward propagating TIDs, but on the other hand, the poleaward TIDs in the American sectors don't show any correlation with changes in E × B drift. However, the initiation process of poleward propagating TIDs originating at the dip equator is not quite clear.…”
Section: Discussion and Summarymentioning
confidence: 99%
See 1 more Smart Citation
“…This storm period has been previously studied and different ionospheric aspects reported on both regional and global scales [ Habarulema et al , , ]. Although the aim of considering 5 days (2 days before and after the storm) was to obtain quiet time reference, most of 7–11 March was disturbed and had storm‐related sources with causes elaborated by Tsurutani et al [].…”
Section: Resultsmentioning
confidence: 99%
“…These TIDs contribute to positive storm effects by moving the F region plasma up to altitudes of low loss rate, thus increasing ionospheric electron density. Recent results showed that TIDs of equator origin can also reach some parts of midlatitudes and contribute to positive storm effects [ Habarulema et al , , ]. Ionospheric response can vary significantly on storm to storm basis [e.g., Field and Rishbeth , ], and excellent reviews about ionospheric storms can be found in Buonsanto [] and Danilov [].…”
Section: Introductionmentioning
confidence: 99%